2020
DOI: 10.21608/ejchem.2020.20908.2245
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/TiO2 nanocomposites: Effect of microwave heating and solution mixing techniques on physical properties

Abstract: C HITOSAN/titanium oxide nanocomposite (CS/TiO 2 nanocomposite) could be prepared by different physical and chemical methods for various applications. CS/TiO 2 nanocomposite has been chemically prepared via microwave heating technique and physically prepared through solution mixing method. Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction spectroscopy (XRD), transmission electron microscopy (TEM) and dynamic light scattering (DLS) were used as spectral tools to characterize the functionality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The growth o the TiO2 NPs in the host blend is thought to cause this attitude. In general, TiO2 NPs hav absorption peaks at wavelengths less than 400 nm, one at around 275 nm and the other in a range from 320 nm to 382 nm, according to the published literature [39,40]. For th nanocomposites of the current study, Figure 5b shows a small peak observed around 27 ± 1.4 nm for all the samples.…”
Section: Interband Transitions Urbach Energy and The Steepness Parame...supporting
confidence: 78%
“…The growth o the TiO2 NPs in the host blend is thought to cause this attitude. In general, TiO2 NPs hav absorption peaks at wavelengths less than 400 nm, one at around 275 nm and the other in a range from 320 nm to 382 nm, according to the published literature [39,40]. For th nanocomposites of the current study, Figure 5b shows a small peak observed around 27 ± 1.4 nm for all the samples.…”
Section: Interband Transitions Urbach Energy and The Steepness Parame...supporting
confidence: 78%
“…TiO 2 -CS bio-nanocomposite has an absorption peak of nearly 257 nm. The absorbance peak was red-shifted in the bio-nanocomposite, which may be ascribed to the surface alteration of TiO 2 NPs generated by the chemical adsorption of CS on the TiO 2 NPs surface [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a similar report, a nanocomposite comprising Ct and magnetic nanoparticles was prepared by performing the functionalization of nanoparticles with carboxylic groups, which allowed the covalent bonding of the nanoparticles with the Ct amine groups [47]. In another report, Ct/TiO 2 nanocomposite was prepared via the outer-sphere complexation reaction between the positive charges of the Ct chains and the negative charges present on the surface of TiO 2 nanoparticles [31]. A related study reported the preparation of starch/multi-walled carbon nanotubes via covalent bond formation between the hydroxyl groups of starch and the groups present on the surface of the nanomaterial [48].…”
Section: Other Methodsmentioning
confidence: 99%
“…Conversely, the surface becomes negatively charged when the solution pH is higher than the pH at PZC. In solutions with pH lower than the pH at PZC of TiO 2 nanoparticles and the pKa of Ct, electrostatic repulsion would occur between the charged surface of the TiO 2 nanoparticles and the chains of Ct, which would enable the complete stretching of the flexible Ct chains, thereby resulting in the dispersion of TiO 2 nanoparticles into the Ct matrix [31].…”
Section: Solution Mixingmentioning
confidence: 99%